The influence of childhood traffic‐related air pollution exposure on asthma, allergy and sensitization: a systematic review and a meta‐analysis of birth cohort studies. Issue 3 (31st December 2014) - Bowatte, G.; Lodge, C.; Lowe, A. J.; Erbas, B.; Perret, J.; Abramson, M. J.; Matheson, M.; Dharmage, S. C.
Abstract The impact of early childhood traffic‐related air pollution (TRAP) exposure on development of asthma and allergies remains unclear. Birth cohort studies are the best available study design to answer this question, but the evidence from such studies has not been synthesized to date. We conducted a systematic review and meta‐analyses of published birth cohort studies to understand the association between early childhood TRAP exposure, and subsequent asthma, allergies and sensitization. Increased longitudinal childhood exposure to PM2.5 and black carbon was associated with increasing risk of subsequent asthma in childhood (PM2.5: OR 1.14, 95%CI 1.00 to 1.30 per 2 μg/m3 and black carbon: OR 1.20, 95%CI 1.05 to 1.38 per 1 × 10−5 m−1). Also, early childhood exposure to TRAP was associated with development of asthma across childhood up to 12 years of age. The magnitude of these associations increased with age, and the pattern was prominent for PM2.5. Increasing exposure to PM2.5 was associated with sensitization to both aero‐ and food allergens. There was some evidence that TRAP was associated with eczema and hay fever. In summary, exposure to TRAP was related to asthma and allergic diseases. However, the substantial variability across studies warrants long‐term birth cohort studies with regular repeated follow‐ups to confirm these findings.